Kultowy ryt z wczesnej epoki żelaza z Altmarku - Müller, Rosemarie (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
Fragment of a vessels with an inside ornament found in a settlement at Arneburg, Kr. Stendal, is described. The engraving represents a stylized „figure of a toad", with mostly Neolithic analogies. Examples of motifs of this kind, occurring on pottery dating from the Bronze Age to the Migration period, are listed. Since the drawing is highly stylized it is not possible to be quite certain whether the archetype was a man or an animal. We do not know, either, if the prototype of these geometrically stylized drawing was identified in the same way by prehistoric man throughout the ages. If this weas the case, a cult lasting through millennia could be surmised. Skeletal remains of toads found in Hallstatt graves may have been linked with a cult. However, it is difficult to solve this problem conclusively.